Advance on the bioactivity and potential applications of dietary fibre from grape pomace. (1st November 2015) - Zhu, Fengmei; Du, Bin; Zheng, Lihong; Li, Jun
Highlights: The biological activities and application of grape pomace dietary fibre were reviewed. The extraction, estimation and chemical composition of grape pomace dietary fibre were also reviewed. It is very important to develop the application of grape pomace by-products in winemaking. Abstract: The winemaking grape pomaces are rich in bioactive phytochemicals and dietary fibre (DF). DFs are phenolic-rich DF matrix and are dietary supplement with benefits on human health. As a result of the increased attention to sustainability of winemaking by-products, efforts have been made to use grape pomace in different bio-industries. In this review, we summarize the existing knowledge on the bioactivity and potential applications of DF from grape pomace, as well as the chemical compositions of DF. Furthermore, the biological activities of DF such as, anti-cancer activity, antibacterial activity, anti-inflammatory activity, antioxidant activity, improving gastrointestinal health activity, anti-apoptotic activity, preventing cardiovascular disease activity, anti-hypercholesterolemic activity, are discussed. Finally, the possible applications and future prospects of grape pomace DF in various fields are also summarised.